Relationship between morphological parameters and throwing velocity, maximal force and swimming speed in elite male water polo players - Kemal Idrizović; Julio Calleja-Gonzáles; Dean Kontić (University of Banja Luka, Faculty of physical education and sport, 2014)
Technical, tactical and physiological demands of water polo players that once were standard are no longer current. The advancement in the total approach to this discipline, from players', coaches' and also from the scientific standpoint, have led to the establishing of new physiological principles that are now actual in this team sport. The relationship of morphological characteristics and specific motor abilities represents one of the important traits of a player profile in elite water polo. The main aim of this study was to examine and define the relationships among the anthropometrical characteristics (body height, arm span, leg length, body mass and BMI) and three sport-specific fitness tests, 20-meters-sprint-swimming, maximal dynamometric force in eggbeater kick and throwing velocity. The sample of participants embraced 22 (23.04 ± 2.72 years) top-quality water polo players, members of the national team and one water polo club, who participated in the Adriatic League competition. Throwing velocity shows a significative correlation only with maximal dynamometric force in eggbeater kick (r=.455, p=.033). Maximal dynamometric force in eggbeater kick, except with throwing velocity shows significative correlation with body mass (r=.745, p=.000), body height (r=.568, p=.006), BMI (r=.521, p=.013) and with arm span (r=.488, p=.021). Regarding to swimming speed, significant correlations were not found. One of the major finding of the present research was that swimming speed has no statistically significant linear correlation with any of applied morphological and specific motor parameters. A second major result was that throwing velocities significantly correlate only with maximal dynamometric force in eggbeater kick. On the other side, no statistically significant correlation has been found between a throwing velocity and the applied anthropometric parameters that almost completely determined a result in the test for the estimation of a maximal dynamometric force in eggbeater kick.